Fcgamma-receptor IIA genotype and invasive pneumococcal infection - Moens, Leen (Clinical immunology (Orlando, Fla.), 2006)
Streptococcus pneumoniae is a major cause of pneumonia, bacteraemia, meningitis, and acute otitis media, especially in young children, immunocompromised patients, and elderly. Fcgamma-IIA receptor plays a crucial role in the phagocytosis of IgG2-opsonized bacteria since it is the sole receptor able to interact with IgG2 antibodies. Fcgamma-RIIA exhibits allelic polymorphisms with different capacities for binding IgG2 and phagocytosis. In a prospective study, we genotyped Fcgamma-RIIA in 55 Caucasian patients suffering from invasive pneumococcal disease and in 100 Caucasian controls. In contrast to previous reports, we found no association between Fcgamma-RIIA genotype and invasive pneumococcal disease